Maraval Reservoir. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Image depicts a view of the Maraval Reservoir, located in the town of Maraval on the island of Trinidad in the Republic of Trinidad and Tobago.
Colour: Shades of Red, Green and Brown; Style: Landscape; Other: Unbordered, Undivided.
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Maraval; Reservoirs--Trinidad and Tobago; Architecture--Trinidad and Tobago; Plants, Potted--Trinidad and Tobago